2013
DOI: 10.1001/2013.jamaophthalmol.221
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Motion by Blind Subjects With the Epiretinal 60-Electrode (Argus II) Retinal Prosthesis

Abstract: To investigate the ability of 28 blind subjects implanted with a 60-electrode Argus II (Second Sight Medical Products Inc) retinal prosthesis system to detect the direction of a moving object.Methods: Blind subjects (bare light perception or worse in both eyes) with retinitis pigmentosa were implanted with the Argus II prosthesis as part of a phase 1/2 feasibility study at multiple clinical sites worldwide. The experiment measured their ability to detect the direction of motion of a high-contrast moving bar on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 12 publications
4
124
0
1
Order By: Relevance
“…To our knowledge, only one other study has reported the identification of motion direction using a similar moving bar task (albeit with a head-mounted camera and with head scanning) in patients implanted with the Argus II device. 22 In that study, most patients were tested using a bar speed of 31.6 deg/s, and because results were reported as a response error in degrees rather than as an accuracy score, we are unable to directly compare our results. Other studies in patients implanted with the Alpha-IMS device also tested motion recognition; however, they used a random sequence of dots on a screen that moved in a certain direction.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, only one other study has reported the identification of motion direction using a similar moving bar task (albeit with a head-mounted camera and with head scanning) in patients implanted with the Argus II device. 22 In that study, most patients were tested using a bar speed of 31.6 deg/s, and because results were reported as a response error in degrees rather than as an accuracy score, we are unable to directly compare our results. Other studies in patients implanted with the Alpha-IMS device also tested motion recognition; however, they used a random sequence of dots on a screen that moved in a certain direction.…”
Section: Discussionmentioning
confidence: 96%
“…7,8 In particular, following the loss of cones, corruption of inner retinal circuits occurs. Although electrical stimulation in blind humans has been shown to elicit the perception of phosphenes through a variety of electrode array placements, 3,9,10 the influence of inner retinal remodeling on achieving optimal visual restoration remains unclear. This is especially important for devices implanted into the subretinal or suprachoroidal space (i.e., farther away from the ganglion cells) because vision restoration using these electrode locations may be influenced more by the local integrity of circuits within the inner retina that need to be traversed before reaching the ganglion cells.…”
mentioning
confidence: 99%
“…15 Twenty-nine patients continued home use of the device. 21 Among the 29 patients, the highest score and highest achieved visual acuity (ranging from logMAR 1.6 to logMAR 2.9) was with a letter reading measured at 20/1262. Furthermore, with the aid of tracing paths on touch screens and auditory feedback, this device had a higher accuracy, but longer times with the implant on promotes the potential learning and reactivating of the visual pathway.…”
Section: Argus IImentioning
confidence: 88%